Pesan Dakwah Majasi untuk Meningkatkan Internalisasi Nilai Islam Pada Generasi Milenial - Mawasti, Wahanani; Surya, Alan (STID Al-Hadid, 2023)
FIGURATIVE DA’WA MESSAGE TO IMPROVE ISLAMIC VALUES INTERNALIZATION OF MILLENIAL GENERATION. The development of da'wah in the 4.0 era gave rise to many millennial preachers who preach via YouTube. Millennial da'wah through YouTube can attract the millennial generation’s interest in studying Islam. This is shown by the number ofuTube video viewers and the positive comments given in the comment column. This article examines how millennial preachers convey messages through the media on YouTube so that they can attract the millennial generation to study Islam. The method used in this study is a literature study through h comparison of lecture videos by 4 millennial preachers. This study shows that millennial preachers have similarities in packaging da'wah messages, namely using a lot of da'wah messages that are figurative in nature, especially figurative language in the form of comparisons. The comparative figure of speech in da'wah messages has a role including: facilitating the millennial generation to understand da'wah material, providing a touch of feeling, not being patronizing so that it is easier for the millennial generation to accept, and facilitating the internalization of values ​​in the millennial generation in da'wah activities via YouTube.